2019
DOI: 10.1038/s41559-019-0913-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparative transcriptomics reveals unique mechanisms underlying extended healthspan in bats

Abstract: Bats are the longest-lived mammals, given their body size. However, the underlying molecular mechanisms of their extended healthspans are poorly understood. To address this question we carried out an eight-year longitudinal study of ageing in longlived bats (Myotis myotis). We deep-sequenced ~1.7 trillion base pairs of RNA from 150 blood samples collected from known aged bats to ascertain the age-related transcriptomic shifts and potential microRNA-directed regulation that occurred. We also compared ageing tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 67 publications
1
72
0
Order By: Relevance
“…We found that the little brown bat (Myotis lucifugus) was an outlier compared to other laurasiatherians with high cancer gene copy numbers, in particular for tumor suppressor genes with both germline and somatic mutations (1.83 copies per ortholog versus 1.42 average for laurasiatherians). Recent comparative studies have suggested that bats in the long-lived genus Myotis do not display telomere shortening with age (Foley et al 2018), showed evidence of positive selection in genes that control DNA damage (Foley et al 2018), and have unique gene expression patterns in pathways controlling DNA repair and tumor suppression that increase with age (Huang et al 2019). Similarly, a previous study found accelerated protein evolution in DNA damage and response pathways that was unique to long-lived mammals (Li and de Magalhães 2013).…”
Section: Discussionmentioning
confidence: 97%
“…We found that the little brown bat (Myotis lucifugus) was an outlier compared to other laurasiatherians with high cancer gene copy numbers, in particular for tumor suppressor genes with both germline and somatic mutations (1.83 copies per ortholog versus 1.42 average for laurasiatherians). Recent comparative studies have suggested that bats in the long-lived genus Myotis do not display telomere shortening with age (Foley et al 2018), showed evidence of positive selection in genes that control DNA damage (Foley et al 2018), and have unique gene expression patterns in pathways controlling DNA repair and tumor suppression that increase with age (Huang et al 2019). Similarly, a previous study found accelerated protein evolution in DNA damage and response pathways that was unique to long-lived mammals (Li and de Magalhães 2013).…”
Section: Discussionmentioning
confidence: 97%
“…extended healthspan 4 , enhanced disease tolerance 3 , vocal communication 5 and sensory perception 6 . To understand the evolution of bats and the molecular basis of these traits, we generated reference-quality genomes for six bat species as part of the Bat1K global genome consortium 1 (http://bat1k.com) in coordination with the Vertebrate Genome Project (https://vertebrategenomesproject.org).…”
mentioning
confidence: 99%
“…Bats have developed a variety of unique biological features that are the rarest among all mammalian, including laryngeal echolocation 4,6 , vocal learning 7 , and the ability to fly 3 . They occupy a broad range of different ecological niches 2 , have an exceptional longevity [8][9][10] and a natural and unique resilience against various pathogenic viruses 1,11 .…”
Section: Figurementioning
confidence: 99%